The Estimate Of Building Maintenance Cost Based On Building Conservation And Maintenance Guide (Permen Number: 24/PRT/M/2008) (Case Study On Kampar Regency Office) - Lidno Fery HS; Rian Trikomara; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Buiiding maintenance in consistent manner has become a requirement that has to be fulfilled. Especially for buildings intended for public service. Rationally, the level of which the building is easy to maintenance will significantly affect the cost every year. considering the problems above, it is therefore required to conduct a study regarding maintenance cost to make system of assessment to help determine priority scale for maintenance of Kampar regency office base on Permen no. 24/PRT/M/2008. It is expected that with this system. The process of maintenance and concervation of Kampar regency office will be make effective and right on target. The cost of the repair was analysis using approximate estimate with the highest unit price per square meter for high rise building from the result of the analysis using the above metho. The repair cost needed is Rp. 289,587,503.16,- with the percentage of damage at 1.62 %. The damage occurred on Kampar regency office is still consired as minor damage which is below. The below percentage required of 30% from maximumconstruction cost for new building. While the maintenance cost is Rp. 2,408,379,210.60,-and increase annually at 7.55% Every years.Keywords: approximate estimate, repair costs, maintenance costs, buildingmaintenance, regency office of Kampar